“Knowledge and Death Penalty Opinion: The Marshall Hypotheses Revisited.” - Lee, Gavin M. (American journal of criminal justice, 2014)
This study tests the three hypotheses derived from the written opinion of Justice Thurgood Marshall in Furman v Georgia in 1972. Subjects completed questionnaires at the beginning and the end of the fall a semester. Experimental group subjects were enrolled in a death penalty class, while control group subjects were enrolled in another criminal justice class. The death penalty class was the experimental stimulus. Findings provided strong support for the first and third hypotheses, i.e., subjects were generally lacking in death penalty knowledge before the experimental stimulus, and death penalty proponents who scored “high” on a retribution index did not change their death penalty opinions despite exposure to death penalty knowledge. Marshall’s second hypothesis--that death penalty knowledge and death penalty support were inversely related--was not supported by the data. Two unexpected findings were that death penalty proponents who scored “low” on a retribution index also did not change their death penalty opinions after becoming more informed about the subject, and that death penalty knowledge did not alter subjects’ initial retributive positions. Suggestions for future research are provided.